Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.5194/nhess-10-1487-2010
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of VLF transmitter signal and Chorus-whistler waves before l'Aquila earthquake occurrence

Abstract: Abstract. We investigate the VLF emissions observed by the Instrument Champ Electrique (ICE) experiment onboard the DEMETER micro-satellite. We analyze intensity level variation 10 days before and after the occurrence of l'Aquila earthquake (EQ). We found a clear decrease of the VLF received signal related to ionospheric whistler mode (mainly Chorus emission) and to signal transmitted by the DFY VLF station in Germany, few days (more than one week) before the earthquake. The VLF power spectral density decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…These electromagnetic waves play a controlling role in the dynamics of Earth's radiation belts, known as the van Allen belts (e.g., Trakhtengerts 1963, Kennel and Petschek 1966, Rycroft 1991, Meredith et al 2001, Thorne et al 2013. It is also important to mention that in the last two decades some authors (e.g., Hayakawa et al 1996, Molchanov and Hayakawa 1998, Němec et al 2009, Rozhnoi et al 2009, Boudjada et al 2010, Písa et al 2013 have used VLF observations to study precursor effects of earthquakes, an active field of research today.…”
Section: Introductionmentioning
confidence: 99%
“…These electromagnetic waves play a controlling role in the dynamics of Earth's radiation belts, known as the van Allen belts (e.g., Trakhtengerts 1963, Kennel and Petschek 1966, Rycroft 1991, Meredith et al 2001, Thorne et al 2013. It is also important to mention that in the last two decades some authors (e.g., Hayakawa et al 1996, Molchanov and Hayakawa 1998, Němec et al 2009, Rozhnoi et al 2009, Boudjada et al 2010, Písa et al 2013 have used VLF observations to study precursor effects of earthquakes, an active field of research today.…”
Section: Introductionmentioning
confidence: 99%
“…They found significant changes in the intensity and, in particular, in the signal-to-noise ratio before the EQ, which is considered to be a precursory ionospheric signature of the EQ. Boudjada et al (2008Boudjada et al ( , 2010 found a similar drop in the natural whistler VLF intensity level a few days before the EQs in the Adriatic region. Using different methods based mainly on the processing of the recorded dynamic spectrum, for each half orbit, authors lead to estimate the maximum of the intensity level through the observed channel frequency of ICE experiment.…”
Section: Detection Of Vlf Natural and Transmitters Signals Above Seismentioning
confidence: 63%
“…Later, several investigations [Rozhnoi et al 2007, Muto et al 2008, Slominska et al 2008] confirmed this drop in VLF intensity. It is important to note that the decrease in the VLF intensity also concerns the natural whistler emissions, as reported by Boudjada et al [2010] for the L'Aquila earthquake (April 6, 2009). Hence, it was seen that the signal of the DFY transmitter was 'damped' from 5 days before to a minimum of one day before the earthquake.…”
Section: Very Low Frequency Transmitter Signals Over Seismic Regionsmentioning
confidence: 85%